Examen especial al componente de cuentas por cobrar de la empresa pública municipal de agua potable y alcantarillado del cantón Sucúa, periodo enero a diciembre 2015 - Samaniego Tello, Lilia Guadalupe (2017)
The Special Examination was carried out on the Accounts Receivable for Customers account, for the period January 1 to December 31, 2015 of the Municipal Public Company of Drinking Water and Sewerage of Cantón Sucúa, entity dedicated to the provision of water and sewage to the city of Sucúa, in the province of Morona Santiago, as a requirement demanded by the Regulation of Academic Regime of the National University of Loja. The investigation is justified because in the EPMAPA-S there have not been internal audits to the Accounts Receivable component, evidencing the existence of a significant amount of economic resources in this area, a situation reflected in the Statement of Financial Position, which promotes the carrying out a Special Exam, which allows detecting the shortcomings in the management of this account, as well as establishing the necessary procedures to improve the internal control of the Company. The execution of the Special Exam to the component of Accounts Receivable in the EPMAPA-S, allowed to evaluate the Internal Control System, verifying if the resources of the company have been managed with the criteria of efficiency, effectiveness and economy, determining the degree of compliance of legal provisions, ordinances and regulations. The development of the examination was carried out considering the phases of Planning, Execution and Communication of Results, issuing a report containing the comments, conclusions and recommendations. Finally, it can be concluded that there is a high rate of delinquency, with deficiencies in the internal control system, which is why some suggestions and recommendations are raised, which empower the improvement of collection efforts to the users of the Company, allowing raising the quality of service delivered to the community of Cantón Sucúa and strengthen its financial stability.